Murder for love - Penzler, Otto; Penzler, Otto. (New York : Delacorte Press, 1996)
From hearts and flowers to erotic obsession, from crimes of passion to the savage gentility of the Victorian gentry, here is love and death in infinite variety, a unique and unprecedented collection of original, never-before-published short mysteries by some of America's bestselling authors. It's the ultimate recipe for love gone wrong, sixteen acclaimed writers - eight men and eight women - offering vastly different perspectives on love, murder, and the opposite sex, in short fiction that proves all great passion lasts a lifetime...however brief that may be.
Keywords: Detective and mystery stories, American; Romance fiction, American; Murder -- Fiction